2015
DOI: 10.2495/ut150231
|View full text |Cite
|
Sign up to set email alerts
|

An ex-ante evaluation of last-mile freight distribution services for city logistics

Abstract: The paper deals with methodologies to support an ex-ante assessment of the impacts generated by the introduction of city logistics measures on last-mile freight distribution services. Some models and algorithms are applied and compared to solve the vehicle routing problem for freight deliveries in the town of Reggio Calabria with the introduction of an urban distribution centre and of green freight vehicles. Heuristic routing algorithms are compared in terms of sequence of clients (retailers) visited subject t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Finally, it may be observed that last-mile and long distance logistics [43,44], microsimulation in the city terminal [45], and urban regeneration aspects [46] are other relevant topics not discussed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it may be observed that last-mile and long distance logistics [43,44], microsimulation in the city terminal [45], and urban regeneration aspects [46] are other relevant topics not discussed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…Last-mile and long distance logistics [4,5], microsimulation in the city terminal [6], and urban regeneration aspects [7] are other relevant topics not discussed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…The proposal is coordinated with the analysis developed in previous works regarding the demand and the supply for freight transport in the city of Reggio Calabria [22,23,25,26].…”
Section: Reggio Calabriamentioning
confidence: 99%
“…The UDC shapes a multi-level scheme in the urban freight distribution process, which allows freight to be carried by means of larger vehicles outside the city and, after the transhipment, by means of smaller and less polluting vehicles inside the city [22,23]. The UDC is the breaking point of the load that fits between the producer and the final customer, adopted by several European countries [24].…”
Section: City Logisticsmentioning
confidence: 99%